2005
DOI: 10.1111/j.1468-1331.2005.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of paclitaxel or cisplatin‐based chemotherapy on sympathetic skin response: a prospective study

Abstract: The current study aimed to assess the viability of sympathetic sudomotor fibers in cancer patients treated with cisplatin or paclitaxel-based chemotherapy and to ascertain whether this method could contribute to the diagnostic sensitivity of conventional techniques. Sympathetic skin response (SSR) from the hand and sole of 23 cancer patients (nine females and 14 males, mean age 62.4 +/- 10.5 years) was recorded unilaterally before and after chemotherapy with six courses of cumulative cisplatin or paclitaxel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Acute and chronic autonomic impairments have deleterious effects on quality of life and survival in health and a variety of disease states [ 3 ]. Initial evidence of cancer- and chemotherapy-related ANS dysfunction have been shown here and in the literature (both during and post-treatment) [ 6 10 , 12 , 30 , 32 , 33 , 43 48 ]. However, the methodology in previous ANS-cancer research has been inconsistent.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Acute and chronic autonomic impairments have deleterious effects on quality of life and survival in health and a variety of disease states [ 3 ]. Initial evidence of cancer- and chemotherapy-related ANS dysfunction have been shown here and in the literature (both during and post-treatment) [ 6 10 , 12 , 30 , 32 , 33 , 43 48 ]. However, the methodology in previous ANS-cancer research has been inconsistent.…”
Section: Discussionmentioning
confidence: 62%
“…In establishing our feasibility criteria (FC), several important factors were weighed. First, previous investigations of ANS function in cancer [ 6 , 8 10 , 12 , 13 , 30 33 ] often had small sample sizes, did not establish pre-treatment baselines, included a wide age-range of participants and lacked sufficient and consistent methodological and results reporting. Second, in accordance with pilot study guidelines [ 24 ], and given that our trial did not include an intervention, we established more stringent FC to reflect the factors that could hinder a larger, more definitive trial.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the authors concluded that sudomotor function is not preferentially affected than somatic fibres in CIPN. 38 Sudoscan, a non-invasive method to quantify the electrochemical skin conductance of limbs, has been applied in a single study enrolling 88 patients receiving various types of chemotherapy to assess sudomotor function to detect and follow-up CIPN. This study supported the use of Sudoscan to assess small fibre neuropathy in patients receiving chemotherapy, but results were too preliminary and obtained just from a single setting to be generalised.…”
Section: Autonomic Function Studiesmentioning
confidence: 99%
“…However, the therapeutic response with the commercial formulation is always associated with toxic side-effects because it contains Cremophor EL, a castor oil/ethanol solution, essential for the paclitaxel solubility but also responsible for most of the side-effects and adverse drug reactions. 2,3 Recently low molecular weight anticancer drugs have been linked to polymers such as hyaluronic acid [4][5][6] (HA), which provide advantages in drug pharmacokinetics 7 and suppresses their undesirable cytotoxic side-effects. HA is a linear polysaccharide formed by alternating D-glucoronic acid (GlcUA) and N-acetyl-D-Glucosamine (GlcNAc) units.…”
Section: Introductionmentioning
confidence: 99%